(untitled) (Research, Society and Development, 2025)
Postpartum depression (PPD) is a disorder that affects mothers after the birth of a newborn, characterized by physiological, biological, and psychological factors in the postpartum period. The general objective of this study is to address postpartum depression, the most relevant aspects of the illness, and nursing intervention strategies. This is a quantitative, retrospective, and descriptive study of women who suffered from PPD. Data was collected through interviews using a questionnaire in the home setting in Manaus, Amazonas, Brazil, containing information about patients diagnosed with postpartum depression and their adherence to treatment. The study sample consisted of women aged 13 to 54 years old. Information was collected from 10 women with diagnoses using a twelve-question questionnaire. The main results obtained are that nursing plays an essential role in emotional care in the postpartum period, focusing on active listening and comprehensive support. It is essential to use tools such as the Edinburgh Postnatal Scale and ensure rapid intervention in severe cases; health is strengthened by the support network and the promotion of self-care. The results suggest that nursing care in postpartum depression includes identifying signs and symptoms early, promoting patients’ mental health, reducing complications, and fostering a strong mother-child relationship. It is concluded that these actions aim to improve mothers’ recovery by creating a supportive environment.